2001
DOI: 10.1111/j.1651-2227.2001.tb01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy in southern Sweden II. Gross motor function and disabilities

Abstract: The gross motor function and disabilities in children with cerebral palsy in southern Sweden were investigated and related to clinical features. The study covered the birth year period 1990‐1993 and comprised 167 children, 145 of them born in Sweden and 22 born abroad. The clinical features and gross motor function were analysed at a mean age of 6.8 y. Clinical features were obtained from a continuing healthcare follow‐up programme. Gross motor function was classified according to the Gross Motor Function Clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
34
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 17 publications
15
34
2
Order By: Relevance
“…These figures are compatible with those in the earlier birth cohorts from 1983 to 1986 and 1987 to 1990 (Hagberg et al , 1996 and also with recent reports from southern Sweden (Nordmark et al 2001). The number of additional neuroimpairments in the individual child was associated with type of CP: children with hemiplegia having the lowest and those with tetraplegia the highest prevalence.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These figures are compatible with those in the earlier birth cohorts from 1983 to 1986 and 1987 to 1990 (Hagberg et al , 1996 and also with recent reports from southern Sweden (Nordmark et al 2001). The number of additional neuroimpairments in the individual child was associated with type of CP: children with hemiplegia having the lowest and those with tetraplegia the highest prevalence.…”
Section: Discussionsupporting
confidence: 80%
“…The children in this study were unequally distributed between the levels of the GMFCS, in contrast to the Canadian report on a stratified random sample of 586 children with CP, where 28% of the children were classified at Level I, 13% at Level II, 19% at Level III, 21% at Level IV, and 19% at Level V (Palisano et al 2000). In the work of Nordmark and colleagues (2001), the distribution between the levels of the GMFCS of 176 children with CP in southern Sweden was more similar to ours, with 41% of the children at Level I, 19% at Level II, 14 % at Level III, 11% at Level IV, and 16% at Level V. The difference between the two Swedish studies (Nordmark et al 2001 and the current study) mainly occurred between Levels III and IV. It may be more difficult to distinguish between these levels in chart review compared with clinical examination, which was the case in the Nordmark study (2001).…”
Section: Discussionmentioning
confidence: 79%
“…The programme included a continuous follow-up of the child's diagnosis, gross motor function, clinical findings and treatment [9,10]. The subtype of CP was determined according to Hagberg et al [11].…”
Section: Methodsmentioning
confidence: 99%
“…Rates of functional limitations in mobility, dexterity, speech, vision and, to a smaller extent, hearing and cognition, have been shown to be associated with GMFCS levels, but not emotion or pain. 22 Others have described associations between levels of the GMFCS and diagnosis, aetiology, intellectual capacity, epilepsy and visual impairment, 25 and bone mineral density; 26 and GMFCS level and learning disability have been shown to be the best predictors of participation restrictions. 17 Investigators with the North American Growth in Cerebral Palsy Project purposely identified a sample of children in GMFCS levels III, IV, and V because they proposed that these children would have higher health care needs, and different patterns of growth and development, than children in levels I and II.…”
Section: Observational Researchmentioning
confidence: 99%
“…40 The samples in these observational studies have been large by the usual standards in developmental research; however, we are not yet able to describe the spectrum of functional limitation in a complete geographically defined population. This work is beginning with clinicians having used the GMFCS to describe disability in Swedish 25 and Latvian 41 populations, and GMFCS data are now routinely collected prospectively by at least one of the CP registers. 42 Information from studies of this type will be useful in determining health, educational, and social service resources required to support children with CP.…”
Section: Observational Researchmentioning
confidence: 99%